A novel first aid stretcher for immobilization and transportation of spine injured patients. - Yan-Sheng Liu (Public Library of Science (PLoS), 2012)
Effective immobilization and transportation are vital to the life-saving acute medical care needed when treating critically injured people. However, the most common types of stretchers used today are wrought with problems that can lead to further medical complications, difficulty in employment and rescue, and ineffective transitions to hospital treatment. Here we report a novel first aid stretcher called the "emergency carpet", which solves these problems with a unique design for spine injured patients. Polyurethane composite material, obtained by a novel process of manually mixing isocyanate and additives, can be poured into a specially designed fabric bag and allowed to harden to form a rigid human-shaped stretcher. The effectiveness of the emergency carpet was examined in the pre-hospital management of victims with spinal fractures. Additionally, it was tested on flat ground and complex terrain as well as in the sea and air. We demonstrated that the emergency carpet can be assembled and solidified on the scene in 5 minutes, providing effective immobilization to the entire injured body. With the protection of the emergency carpet, none of the 20 patients, who were finally confirmed to have spinal column fracture or dislocation, had any neurological deterioration during transportation. Furthermore, the carpet can be handled and transported by multiple means under differing conditions, without compromising immobilization. Finally, the emergency carpet allows the critically injured patient to receive multiple examinations such as X-ray, CT, and MRI without being removed from the carpet. Our results demonstrate that the emergency carpet has ideal capabilities for immobilization, extrication, and transportation of the spine injured patients. Compared with other stretchers, it allows for better mobility, effective immobilization, remarkable conformity to the body, and various means for transportation. The emergency carpet is promising for its intrinsic advantages in the pre-hospital management of accident victims.